Geotouristic attractions of the Saaremaa Island according to the opinions of tourists. - Łach, Janusz (Geotourism/Geoturystyka, 2018)
The article presents chosen geotouristic attractions of Saaremaa. High landscape values and touristic attractiveness are typical of the island. They may be observed in the Vilsandi National Park with rich fauna and fl ora, and geological and morphological forms, together with historic mills, houses, military objects from the 1st and 2nd world wars and industrial objects connected with recent fi shing in the area. Rocky cliffs and the highest cliff in Saaremaa – Panga – as well as the meteorite lake Kaali are other objects with high touristic attractiveness located on a geotouristic trail. Medieval churches from the 12th and 13th centuries and the impressive Kuressaare castle also draw tourists’ attention. The architecture of those buildings refl ects the geological history of the island. As a result of fi eld works, the an understanding of the motivation behind the visitors to the Saarte Geopark was obtained. As such, the author was able to determine their touristic profi le. On the basis of their opinions, an analysis and evaluation of touristic development and touristic attractions infl uencing geotouristic attractiveness of the island was conducted. // W artykule przedstawiono wybrane miejsca geoturystyczne Saaremy, które obok wysokich walorów krajobrazowych wyróżniają się dużą atrakcyjnością turystyczną. Należą do niej m.in. Vilsandi National Park, z bogatą fl orą i fauną, formami geologicznymi i morfologicznymi, z zabytkowymi wiatrakami, domami, obiektami militarnymi z I i II wojny światowej oraz obiektami przemysłowymi związanymi z niedawno jeszcze praktykowanym rybołówstwem. Następnymi obiektami o wysokiej atrakcyjności turystycznej, położonymi na szlaku geoturystycznym, są skalne klify z najwyższym klifem Saremy, Pangą oraz wielka osobliwość przyrodnicza, którą jest jezioro meteorytowe Kaali. Na uwagę zasługują pochodzące z XII i XIII wieku średniowieczne kościoły oraz imponujący zamek w Kuressaare, zawierające w materiałach, z których są zbudowane historię geologiczną wyspy. W wyniku prac terenowych uzyskano wiedzę dotyczącą motywacji odwiedzających Saarte Geopark. W ten sposób określono ich profi l turystyczny. Na podstawie opinii turystów dokonano analizy i oceny zagospodarowania turystycznego oraz walorów turystycznych wpływających na atrakcyjność geoturystyczną wyspy.